Socket augmentation - Shalu Chandna (Journal of International Clinical Dental Research Organization, 2015)
Introduction of dental implants have come to the forefront of modern odontology. A successful osseointegration demands an ideal quantity and quality of alveolar bone. Socket augmentation techniques are effective in minimizing postextraction alveolar ridge resorption. The aim of this paper is to review the available literature on socket augmentation with special focus on its relation with implant.